Diaspora in the homeland: homeland perceptions regarding diaspora Jews in Israel's discourse around its collective identity - Abu, Ofir (Ethnic and racial studies, 2022)
Homeland-construed perceptions of the diaspora can yield valuable insights into the discourse around the homeland's collective identity. I illustrate this claim using the debate surrounding the Kotel Compromise, a government plan designed to regulate pluralistic and non-Orthodox Jewish prayer at the Western Wall (Kotel in Hebrew). This plan has recently become a subject of contention between the State of Israel, where Orthodox Judaism has an institutional monopoly, and Diaspora Jews, many of whom identify with non-Orthodox Jewish denominations, such as Reform and Conservative Judaism. Drawing on protocols of the Knesset (Israeli parliament), I show how the different participants in this debate used their perceptions of Diaspora Jews not only to reaffirm external boundaries relating to Jewish peoplehood, but also to reconstruct internal boundaries relating to Judaism as religion. This paper suggests that analyzing homeland perceptions of the diaspora can widen our understanding of the construction of homeland identities and boundaries.